Poor obstetric outcomes in Indian women with Takayasu arteritis - Latika Gupta; Durga Prasanna Misra; Sakir Ahmed; Avinash Jain; Abhishek Zanwar; Able Lawrence; Vikas Agarwal; Amita Aggarwal; Ramnath Misra (Advances in Rheumatology, 2020)
Abstract Introduction Takayasu’s arteritis (TA) affects young women in the childbearing age group. We studied obstetric outcomes in these patients before and after disease onset. Methods Women aged more than 18 years with Takayasu’s arteritis (ACR 1990 criteria) were included. Demographic data, clinical features, disease activity using Indian Takayasu Arteritis clinical score (ITAS), Disease Extent Index for TA (DEI.TaK) and damage assessment using TA Damage score (TA), history of conception and maternal and fetal outcomes were recorded from hospital records and telephonic interview. Results are in median and IQR. Results Of the 64 women interviewed, aged 29 (24–38) years and disease duration 5 (4–10) years, 74 and 38 pregnancies had occurred before and after disease diagnosis in 29 and 20 women respectively. In eight, the diagnosis was made during pregnancy. Age at disease onset was 22 (18–30) years. Type 5 disease was the most common (n = 32, 59.3%), and an equal number of patients had Ishikawa’s class I and II disease (n = 26, 40.6%). Median ITAS (n = 44) was 13 (7–16), DEI.Tak 12.5 (9–16.75) and TADS 8 (6.5–10). Twenty-five patients wanted to get pregnant, of which 8 (32%) did not do so because of their disease. Fifteen were unmarried of whom 6 did not marry due to disease. Obstetric outcomes were poorer in pregnancies that occurred after the onset of disease as compared with those before it (RR = 1.5, p = 0.01). Pregnancies after the onset of TA carried a very high risk of maternal [RR3.9 (1.8–8.5), P < 0.001] as well as fetal complications [RR = 2.0 (1.2–3.4), p = 0.001]. Hypertension was the most common maternal complication and occurred most often in the last trimester. The baby weight at birth was lower in pregnancies after disease (2.3 vs. 3.0, p = 0.01). Wong’s score greater than or equal to 4 predicted lower birth weight (p = 0.04). ITAS, ITAS-A, DEI. Tak and TADS could not predict obstetric outcomes, and ITAS score exhibited moderate correlation with DEI. Tak (r = 0.78) and TADS (r = 0.58). Conclusion Women with TA suffer from extremely high risk of poor maternal and foetal outcomes. Wong’s scoring can be useful to predict birth weight.